The Effect of Work Ethics, Work Discipline And Service on The Satisfaction of Members of The Karya Sentosa Market Traders Cooperative (Koperasi Pedagang Pasar Karya Sentosa) in Batu City - Lediana Mbeo; Mohamad Rifa’i; Anung Prasetyo Nugroho (International Journal of Management and Business, 2025)
This study aims to determine the influence of work ethics, work discipline, and service quality on the satisfaction of members of the Karya Sentosa Market Traders Cooperative in Batu City, individually and collectively. A quantitative research approach was employed in this study. The sample was selected using a non-probability sampling method, resulting in 67 respondents who are members of the cooperative. Data were collected through a questionnaire, while the analysis was conducted using multiple linear regression with the assistance of SPSS 25 software. The findings of this study indicate that work ethics significantly impact the members' satisfaction, as evidenced by a t-value of 4.746. Similarly, work discipline significantly influences the members' satisfaction, with a t-value of 3.853, while service quality also has a significant effect, with a t-value of 5.031. Furthermore, the simultaneous analysis reveals that work ethics, work discipline, and service quality collectively substantially impact the members' satisfaction, with an F-calculated value of 19.868 or 80.4%. These results suggest maintaining strong work ethics, enforcing work discipline, and providing high-quality service can enhance member satisfaction.